Effect of antibiotics and anti-inflammatory agents on the purified protein derivative response in the rat - Kabakus, N; Kalkan, A; Felek, S; Yilmaz, B; Mogulkoç, R; Baltaci, A; Kiliç, SS (Scandinavian University Press, 1999)
We investigated the effects of several antibiotics and anti-inflammatory agents on the purified protein derivative (PPD) response in the rat. Animals mere immunized with Mycobacterium bovis vaccine BCG. Antibiotics and anti-inflammatory drugs were administered at therapeutic doses for 10 d, Chloramphenicol, erythromycin, aspirin and ibuprofen suppressed the PPD response, but penicillin and acetaminophen had no significant effects.
Keywords: Tuberculin